Supermatrix phylogeny and biogeography of the Australasian Meliphagides radiation (Aves: Passeriformes) - Marki, Petter Z.; Jønsson, Knud A.; Irestedt, Martin; Nguyen, Jacqueline M.T.; Rahbek, Carsten; Fjeldså, Jon (Molecular phylogenetics and evolution, 2017)
[Display omitted] •A dated supermatrix phylogeny of the avian infraorder Meliphagides.•Sampling of 286 of 289 currently recognized species (99% complete) within the Meliphagides.•60 newly sequenced species of Meliphagides.•The Meliphagides likely originated in Australia in the early Oligocene.•Frequent exchanges between regions, particularly among honeyeaters (Family: Meliphagidae) With nearly 300 species, the infraorder Meliphagides represents one of the largest and most conspicuous Australasian bird radiations. Although the group has been the focus of a number of recent phylogenetic studies, a comprehensive species-level phylogenetic hypothesis is still lacking. This has impeded the assessment of broad-scale evolutionary, biogeographic and ecological hypotheses. In the present study, we use a supermatrix approach including five mitochondrial and four nuclear markers to infer a time-calibrated phylogeny of the Meliphagides. Our phylogeny, which includes 286 of the 289 (99%) currently recognized species, is largely congruent with previous estimates. However, the addition of 60 newly sequenced species reveals some novel relationships. Our biogeographic analyses suggest an Australian origin for the group in the early Oligocene (31.3Mya, 95% HPD 25.2–38.2Mya). In addition, we find that dispersal events out of Australia have been numerous and frequent, particularly to New Guinea, which has also been the source of multiple back-colonizations to the Australian mainland. The phylogeny provides an important framework for studying a wide variety of macroecological and macroevolutionary themes, including character evolution, origin and timing of diversification, biogeographic patterns and species responses to climate change.